The Tagus River delta landslide, off Lisbon, Portugal. Implications for Marine geo-hazards - Terrinha, Pedro (2019)
The stratigraphy of the Tagus river ebb-tidal delta off Lisbon (Portugal) is investigated using high resolution multichannel seismic reflection profiles with the purpose of searching for sedimentary or erosive features associated with landslides. The Tagus delta is sub-divided in two prograding seismic units of 17 ky to 13 ky and 13 ky to Present based on the calibration of seismic lines using gravity and box-cores in the Tagus pro-delta. We report the existence of a buried landslide with 11 km of length, 3.5 km of width and a maximum thickness of 20 m that accounted for the collapse of half of the upper unit of the Tagus river delta front in Holocene times. The non-collapsed half of the delta front contains extensive shallow gas of still unknown origin and nature. An estimated age of ~8 ky BP for the Tagus delta landslide is proposed based on stratigraphic correlation. The trigger mechanisms of the newly identified Tagus landslide are discussed as well as of the several landslides also found in the lower delta unit. These findings present a first step towards a future assessment of the susceptibility of the nearby coastal areas and the off-shore infrastructures to hazards related to such large collapses.